Identifying, Prioritizing and Bundling Innovations: Empowering Women as Partners and Drivers of Climate Change Solution - Mukhopadhyay, Prama; Puskur, Ranjitha; Chadha, Deepali; Ketema, Dessalegn Molla; Lutomia, Cosmas Kweyu; Nchanji, Eileen; Gartaula, Hom N. (CGIAR System Organization, 2023)
Climate change has major implications for food security and the livelihood of smallholder farmers, especially in low- and middle-income countries (LMICs). This is so in spite of the technical and technological innovations in agri-food systems over the past few decades which not only aimed to boost productivity but also be more climate smart. Evidence also suggests that the impact of climate change is not gender neutral (UN Women 2022). Recent studies reveal that many sustainable agricultural technologies remain out of the reach of women, especially those from most marginalized communities, not only due to prevalent gendered social norms but also because women are not considered a ‘target group’ while designing these technologies (Nelson and Huyer 2016; Terefe and Williams 2021). Therefore, women in the global south seem to have a lower uptake of climate-smart agriculture (CSA) technologies.